Early surgical management of severe liver trauma with vascular complication can lead to early discharge. (July 2020) - Ban, Ee Jun; Hii, Belinda; Smith, Marty; Clements, Warren
Intrahepatic arterio-portal fistulas are rare complications of blunt hepatic trauma. We describe a case of a 35-year-old male sustaining blunt abdominal trauma resulting in a grade IV liver injury complicated by arterio-portal fistula, portal venous pseudoaneurysm and concomitant bile duct injury. Although arterial embolisation is the mainstay of treatment for arterio-portal fistula, we describe a rationale for early involvement of a hepatobiliary surgeon for multidisciplinary management. Hepatic resection for acute hepatic trauma can, in selected cases, promptly manage all elements of portal triad injury, and in this particular case facilitated early uncomplicated discharge.